2018
DOI: 10.1175/waf-d-17-0104.1
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Verification of Storm Prediction Center Convective Outlooks

Abstract: Eight years’ worth of day 1 and 4.5 years’ worth of day 2–3 probabilistic convective outlooks from the Storm Prediction Center (SPC) are converted to probability grids spanning the continental United States (CONUS). These results are then evaluated using standard probabilistic forecast metrics including the Brier skill score and reliability diagrams. Forecasts are gridded in two different ways: one with a high-resolution grid and interpolation between probability contours and another on an 80-km-spaced grid wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 46 publications
4
41
0
Order By: Relevance
“…For Day 4 and beyond, only 15% and 30% contours are issued, and for significant severe risk, only a single 10% contour is drawn. For more information on SPC's forecasting process, including historical changes to severe weather and product definitions, see Hitchens and Brooks (2014), Edwards et al (2015), or Herman et al (2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For Day 4 and beyond, only 15% and 30% contours are issued, and for significant severe risk, only a single 10% contour is drawn. For more information on SPC's forecasting process, including historical changes to severe weather and product definitions, see Hitchens and Brooks (2014), Edwards et al (2015), or Herman et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hitchens and Brooks (2012) investigated the skill of Day 1 categorical outlooks, and this effort was expanded to include evaluation of Days 2 and 3-among other additions-in Hitchens and Brooks (2014). Early published efforts to verify SPC's convective outlooks probabilistically (e.g., Kay and Brooks 2000) have received renewed attention in Hitchens and Brooks (2017) and more formally in Herman et al (2018). Collectively, these studies have demonstrated improving skill in short-to medium-range severe weather forecasts in association with improved numerical weather prediction (NWP), though advances have been stagnating somewhat in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, storm‐scale outputs from convection permitting models provide short‐range (e.g., 12–36 hr) forecast guidance (Gallo et al, , ). Accurately forecasting severe weather events remains a challenging task, but skill of SPC days 1–3 forecasts for severe convective storms has been increasing since the mid‐1990s (Herman et al, ; Hitchens & Brooks, ; ; Hitchens et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…From an operational perspective, early modern forecasts for SCS events were confined to the same or next day (Grice et al 1999), but it is now commonplace to see official forecast outlooks for SCSs-issued by the NOAA/NWS's Storm Prediction Center (SPC)-with leads of 4-8 days. SPC forecasts have shown increasing skill with respect to time since the mid-1990s (Hitchens andBrooks 2012, 2014;Herman et al 2018); however, consistent skillful forecasts of daily tornado and hail activity are not likely to be found beyond day 9 and 12, respectively, if solely using current atmospheric numerical weather prediction systems (Gensini and Tippett 2019). Despite the limitations of dynamical prediction, other subseasonal forecasting techniques can act as a "bridge" to extend prediction beyond the traditional limits of NWP (Zhang 2013).…”
mentioning
confidence: 99%